Mutual Caring—Resolving Habituation Through Awareness: Supporting Meaningful Learning From Projects. Issue 2 (7th April 2014) - Jugdev, Kam; Wishart, Paul
ABSTRACT: This study used Grounded Theory methodology and developed an emergent theory of Mutual Caring . The main concern was Habituation to ineffective lessons learned sharing practices. Habituation is resolved through Mutual Caring, a socially and psychologically adaptive process. Mutual Caring involves comfortable conversations, engaging/sharing, and developing self‐confidence, resulting in an enhanced wisdom pool. This paper extends the emphasis on tangible knowledge‐sharing mechanisms. Mutual Caring could lead to better outcomes, such as more accessible and usable knowledge, a project management wisdom pool, and criteria for improved dyadic relationships to enhance project learning.